PROSES MANUFAKTUR MESIN PERONTOK BIJI SORGUM - Oka Firdaus (2022)
Sorghum is a type of grain crop that can be cultivated well in dry areas and areas with high rainfall intensity. Almost all parts of this sorghum plant can be utilized, one of the most important parts that can be processed is the seed part of the sorghum plant. This sorghum seed threshing machine is designed to assist sorghum plant farmers in processing their crops, namely by facilitating the separation process between fruit petals and sorghum seeds with maximum yield quality. The method used in this research is by conducting literature studies, field studies, concept design processes, manufacturing process selection, manufacturing processes, trials, and formulation of results. The sorghum seed threshing machine has dimensions (LxWxH) 125x50x134 cm. With several main components, namely the frame, in and out hoppers, thresher teeth, filters, motors, and fans. The main drive of this sorghum seed threshing machine is a gasoline motor with a power of 5.5 hp, and the engine speed is channeled through pulleys and belts. The pulley measures 4 inches as the driving pulley and 12 inches for the driven pulley, and the belt is 1,520 m long. And the results of the machine that the author has made has a threshing capacity of 307.59 kg/hour with a threshing yield of 82%.